Human intelligence and polymorphisms in the DNA methyltransferase genes involved in epigenetic marking. - Paul Haggarty; Gwen Hoad; Sarah E Harris; John M Starr; Helen C Fox; Ian J Deary; Lawrence J Whalley (PLoS ONE)
Epigenetic mechanisms have been implicated in syndromes associated with mental impairment but little is known about the role of epigenetics in determining the normal variation in human intelligence. We measured polymorphisms in four DNA methyltransferases (DNMT1, DNMT3A, DNMT3B and DNMT3L) involved in epigenetic marking and related these to childhood and adult general intelligence in a population (n = 1542) consisting of two Scottish cohorts born in 1936 and residing in Lothian (n = 1075) or Aberdeen (n = 467). All subjects had taken the same test of intelligence at age 11yrs. The Lothian cohort took the test again at age 70yrs. The minor T allele of DNMT3L SNP 11330C>T (rs7354779) allele was associated with a higher standardised childhood intelligence score; greatest effect in the dominant analysis but also significant in the additive model (coefficient = 1.40(additive); 95%CI 0.22,2.59; p = 0.020 and 1.99(dominant); 95%CI 0.55,3.43; p = 0.007). The DNMT3L C allele was associated with an increased risk of being below average intelligence (OR 1.25(additive); 95%CI 1.05,1.51; p = 0.011 and OR 1.37(dominant); 95%CI 1.11,1.68; p = 0.003), and being in the lowest 40(th) (p(additive) = 0.009; p(dominant) = 0.002) and lowest 30(th) (p(additive) = 0.004; p(dominant) = 0.002) centiles for intelligence. After Bonferroni correction for the number variants tested the link between DNMT3L 11330C>T and childhood intelligence remained significant by linear regression and centile analysis; only the additive regression model was borderline significant. Adult intelligence was similarly linked to the DNMT3L variant but this analysis was limited by the numbers studied and nature of the test and the association was not significant after Bonferroni correction. We believe that the role of epigenetics in the normal variation in human intelligence merits further study and that this novel finding should be tested in other cohorts.